A multiplex PCR method for identification of two common true cutworm species (Lepidoptera: Noctuidae) tested in the central plain of Guilan province, Iran - Hosseini, Reza; Madahi, Khadijeh (Zootaxa, 2018)
Many species of cutworms (Lepidoptera: Noctuidae) are important agricultural pest. They feed on roots and foliage of their host plants. Traditionally these species are identified based on morphological characteristics of adults. Hence identification of specimens in poor condition, immature stages and also closely related species or cryptic species is a difficult task. The basics of biological and ecological studies largely rely on an accurate species identification; consequently these investigations are impacted by potential misidentifications. In this study, we amplified 5' region of mitochondrial c cytochrome oxidase subunit I (COI) gene (DNA barcode region) of various common true cutworm species including Agrotis ipsilon (Hufnagel, 1766), Agrotis exclamationis (Linnaeus, 1758), Peridroma saucia (Hübner, 1808) and Xestia c-nigrum (Linnaeus, 1758) from agricultural fields of Guilan province (North of Iran). We were able to detect 66 conservative Single Nucleotide Polymorphisms (SNPs) among the targeted pest species and eventually design specific primers and develop a multiplex polymerase chain reaction assay as a molecular diagnostic tool for immature stages of two the most common and abundant species including A. ipsilon and X. c-nigrum in Guilan province.